Increased literacy scores for Indigenous children in schools using the cross-curriculum priority - Skelton, F (Department of Social Services, 2016)
Results from Footprints in Time: the Longitudinal Study of Indigenous Children (LSIC) indicate that children attending schools using the Aboriginal and Torres Strait Islander histories and cultures cross-curriculum priority have higher average literacy scores than children in schools that do not.
National Centre for Longitudinal Data Research Summaries
Keywords: Culture -- Indigenous; Education and Training -- Literacy and numeracy; Learning, education and training; Education and Training; Culture; Indigenous; Literacy and numeracy; Learning, education and training